London rules eaudiobook - Herron, Mick (Slough House, 2018)
At MI5 headquarters Regent's Park, First Desk Claude Whelan is facing attacks from all directions: the MP who orchestrated the Brexit vote, a nasty tabloid columnist, and the frontrunner for mayor of the West Midlands. Meanwhile, the country is suffering a seemingly random string of terror attacks. Over at Slough House, the home for demoted MI5 spies, the agents are struggling with personal problems, from repressed grief to a possibly psychopathic new colleague. But they're about to rediscover their greatest strength—that of making a bad situation much, much worse.